2008
DOI: 10.1111/j.1574-695x.2008.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of the acidic repeat protein (arp) gene differentiates venereal from nonvenerealTreponema pallidumsubspecies, and the gene has evolved under strong positive selection in the subspecies that causes syphilis

Abstract: Despite the completion of the Treponema pallidum genome project, only minor genetic differences have been found between the subspecies that cause venereal syphilis (ssp. pallidum) and the nonvenereal diseases yaws (ssp. pertenue) and bejel (ssp. endemicum). In this paper, we describe sequence variation in the arp gene which allows straightforward differentiation of ssp. pallidum from the nonvenereal subspecies. We also present evidence that this region is subject to positive selection in ssp. pallidum, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 39 publications
9
59
0
Order By: Relevance
“…The analytic sensitivity of the real-time quadriplex PCR assay was determined using 10-fold serial dilutions of purified TPpertenue genomic DNA (CDC-1 strain). The analytical specificity of the PCR assay was verified using DNA purified from 10 laboratory strains of TP-pallidum 8,9 (Nichols, SS 14, Mexico A, JV1, DAL-1, Madras, 1 strain from Maryland, 3 strains from Minnesota) and 11 clinical strains from South Africa, 11 13 laboratory strains of TP-pertenue 8,9 (CDC-1, CDC-2, CDC-2575, Samoa D, Samoa F, Ghana 051, Gauthier, and 6 strains from Indonesia), a clinical strain from Democratic Republic of the Congo, 6 and 2 strains of TP-endemicum (Bosnia A and Iraq B). In addition, a previously used panel of nonpathogenic treponemes (T. denticola, T. refringens, and T. phagedenis) and other microorganisms was included to determine the specificity of the assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytic sensitivity of the real-time quadriplex PCR assay was determined using 10-fold serial dilutions of purified TPpertenue genomic DNA (CDC-1 strain). The analytical specificity of the PCR assay was verified using DNA purified from 10 laboratory strains of TP-pallidum 8,9 (Nichols, SS 14, Mexico A, JV1, DAL-1, Madras, 1 strain from Maryland, 3 strains from Minnesota) and 11 clinical strains from South Africa, 11 13 laboratory strains of TP-pertenue 8,9 (CDC-1, CDC-2, CDC-2575, Samoa D, Samoa F, Ghana 051, Gauthier, and 6 strains from Indonesia), a clinical strain from Democratic Republic of the Congo, 6 and 2 strains of TP-endemicum (Bosnia A and Iraq B). In addition, a previously used panel of nonpathogenic treponemes (T. denticola, T. refringens, and T. phagedenis) and other microorganisms was included to determine the specificity of the assay.…”
Section: Methodsmentioning
confidence: 99%
“…However, subspecies-specific genetic signatures permit molecular differentiation using methods that involve polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP), and DNA sequencing. 3,[6][7][8][9] These existing molecular methods are inherently technically complex resulting in inevitable delays in reporting results. We therefore developed a TaqMan-based real-time quadriplex PCR assay to rapidly and simultaneously differentiate between TP-pallidum, TPpertenue, and TP-endemicum in a single test that can be used for screening and investigation of individual cases.…”
Section: Introductionmentioning
confidence: 99%
“…The TPE0326 gene, which encodes a treponemal ␤-barrel assembly machinery A (BamA) ortholog, and the arp gene, shown to contain a 60-bp repetitive sequence in its central region and to code for a fibronectin-binding protein, were also identified as worthy of further investigation (110,117,118). The arp gene had been previously reported by Harper et al (95) to contain up to four different types of 60-bp repetitive sequences (named types I, II, II-III, and III) in T. pallidum subsp. pallidum isolates, while T. pallidum subsp.…”
Section: Genetic Diversity and Pathogenesis Of Human Treponematosesmentioning
confidence: 99%
“…It was hypothesized that these genetic differences among subspecies might be related to the different clinical manifestations of these diseases and support the classification of the T. pallidum subspecies into distinct groups (95)(96)(97)(98)(99). Phylogenetic analysis using genomic data only partially helped to solve the complex problem of the origin of treponematoses.…”
Section: The Unitarian Hypothesismentioning
confidence: 99%
“…With regard to the arp gene (Pillay et al, 1998), a variable number of tandem repetitions were found in the tested genomes. Based on amino acid variations, previously published papers (Harper et al, 2008b;Liu et al, 2007) classified the TPA and TPE Arp repeat motifs into 4 types (I, II, III, II/III), and the variability in repeat sequence types correlated with the sexual transmission strategy (Harper et al, 2008b). The differences among tested strains were also found in a number of 24 bp tandem repeats of TP0470, a gene encoding a hypothetical protein, and in indels present in the hypothetical TP0967 gene (Mikalová et al, 2010).…”
Section: Whole Genome Fingerprintingmentioning
confidence: 99%